UTILIZATION OF WASTE HEAT FROM TECHNOLOGICAL EQUIPMENT TO IMPROVE THE ENERGY EFFICIENCY OF VENTILATION SYSTEMS - Prytula, N.; Bezhyk, O. (Energy and Automation, 2025)
The article analyzes various possibilities for utilizing waste heat removed from installed equipment at industrial enterprises. A comparison of different types of systems is presented, highlighting their advantages and disadvantages. Calculations using the h–d diagram were carried out for different outdoor air temperatures for three system configurations: a straight-through system (without heat recovery), a system with air recirculation, and a system with a two-level mixing chamber. The advantages of using an adaptive system with a two-level mixing chamber compared to the traditional air recirculation scheme are demonstrated. It is shown that, under certain operating modes, the adaptive system can reduce operational costs by more than 10 times. Technical barriers to the implementation of an adaptive system with a two-level mixing chamber are also discussed. Key words: energy efficiency; adaptive system; air recirculation; heat recovery